O impacto das medidas técnicas sobre as exportações brasileiras de papel e celulose. - Pereira, Franciele de Oliveira (Universidade Federal de São Carlos, 2014)
The aim of this study is to assess the potential effects of technical measures belong to the WTO TBT agreement on exports of Brazilian pulp and paper industry. The choice of this segment was due to the same consist of a major component of national export agenda, being susceptible to external regulations. For this, we employed a gravity model comprising Brazil and its importers who reported at least one technical measure within the analysis period 1997-2012. The econometric model, whose inference occurs through the Tobit method further comprises the GDP of the countries involved in trade , foreign tariffs for products affected, bilateral distances and the official languages of each of the trading partners considered. Through descriptive and statistical analyzes we found that greater attention is given to papers and supplies intended for toilet use and the information content present in these seems to be a decisive factor in purchasing their partners. The effect of technical measures on the segment revealed that some of the measures imposed are associated with lower export volumes, thus suggesting greater trade between the same restriction as notifications to the production processes on the product, as well as measures involving compliance which can influence the cost structure of exporting in an effort to adapt its products. Thus, it is expected that the results found to contribute to greater understanding of the effect of technical measures on the pulp and paper industry, as well as the behavior of these requirements over others products of agribusiness.
The impact of technical measures on the brazilian exports of the pulp and paper.
Keywords: exportação - Brasil; modelos econométricos; comércio exterior regulamentação; medidas técnicas; modelo gravitacional; papel e celulose; technical measures; gravity model; pulp and paper; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA INTERNACIONAL